POTENSI PENGEMBANGAN SORGUM SEBAGAI PANGAN ALTERNATIF, PAKAN TERNAK DAN BIOENERGI DI ACEH - Elvira Sari Dewi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This study aims to introduce sorghum and its potential as an alternative food, fodder and also a source of energy in the form of bioethanol. This activity targets the absence of accurate information about the sorghum varieties suitable for all of the end product of sorghum. Adaptability allows sorghum to be planted on marginal lands without having to compete against the land with important agricultural crops. The observed variables including generative morphological traits and yield components and the potential of bioethanol will be produced. The study of variables of the generative traits (plant height, panicle length, and panicle weight) and yield components (weight of 100 seeds / plot and seed dry weight / plot) shows that the three varieties tested responded well to the environment is growing. Varieties Pahat indicates growth response and the best results followed by Kawali and UPCA. Pahat is more likely to be studied and developed in Aceh.